Pengembangan Panduan Pelatihan Keterampilan Mengelola Emosi sebagai Upaya Preventif Perilaku Bullying Siswa Sekolah Menengah Pertama - Luthfita Cahya Irani; Dany Moenindyah Handarini; Lutfi Fauzan (Jurnal Kajian Bimbingan dan Konseling, 2018)
Abstract: This study aims to develop a training guide in emotion management skills to prevent bullying behavior. The method used is the research and development model for junior high school students. The trial subjects in this study included guidance and counseling experts, psychology experts, educational technology expert, and school counselors. Instruments used are the scale of emotion management skills for students, expert assessment instruments and counselors assessment instruments. Data from the assessment of guidance and counseling experts, psychology experts, educational technology expert, and three school counselors from three different schools in Malang showed that the developed product is acceptable and feasible to be used for the improvement of emotion management skills as a preventative effort of bullying behavior for junior high school students.